Aktivitas harian kadal Eutropis multifasciata pada habitat kebun di dataran rendah di Desa Peguyangan, Denpasar – Bali - Puspita Dewi, Ni Luh Putu Gina; Yuni, Luh Putu Eswaryanti Kusuma; Suaskara, Ida Bagus Made (Jurnal Biologi Udayana; Vol 24 No 2 (2020): JURNAL BIOLOGI UDAYANA, 2020)
Common Sun Skink Eutropis multifasciata is one species of ectothermic animal, whose body temperature is affected by the temperature of their surrounding environment. This study aims to determine the daily activity of lizards Eutropis multifasciata that live in the lowlands. This research was conducted from 27 March to 07 May 2019 in a plantation habitat with a dense cover at an altitude of 64 masl. Observations were made using focal animal sampling method with instantaneous recording. For each individual lizard found, its activity was observed for five (5) minutes with a ten (10) seconds time interval. Observation of activities carried out throughout the day, starting at 07.00 until 17.00 WITA. There were no significant differences in daily activities between male and female Eutropis multifasciata lizards. Percentage of the most widely performed activities was foraging with an average of 35.15% while the least performed activities was shuttling with an average of 0.68%. The percentage of other activities were moving 24.10%, overt basking 19.62%, covert basking 14.29%, cooling 4.69%, and aggression 1.48%.